Role of Deep Fluid Injection in Induced Seismicity in the Delaware Basin, West Texas and Southeast New Mexico - K. M. Smye; J. Ge; A. Calle; A. Morris; E. A. Horne; R. L. Eastwood; R. Darvari; J. P. Nicot; P. Hennings (Geochemistry, Geophysics, Geosystems)
Abstract Rates of seismicity in the Delaware Basin of Texas and New Mexico increased from 10 earthquakes per year of local magnitude (ML) 3.0 and above in 2017 to more than 185 in 2022, coincident with increasing oil and gas production and wastewater re‐injection into strata shallow or deeper than producing intervals. Events of large magnitude—up to ML 5.4 to‐date—occur on faults extending into formations above the basement that have received more than four billion barrels of injection. Here, we demonstrate the link between injection geology, pore pressure evolution, fault stability, and induced seismicity in this region. We find that the injection targets are largely dolomitized platform carbonates with low (<5 vol.%) matrix porosity and fracture‐enhanced permeability with inherent heterogeneity in flow properties. A comprehensive, three‐dimensional geological model populated with reservoir properties is used for fluid flow modeling, with global calibration supplemented by dynamic injectivity data. Pore pressure changes with deep injection are up to 5 MPa from 1983 to 2023, increasing the native pore pressure state by 10% locally. Modeling results show that earthquakes occurring at distances of up to 30 km from deep injection have experienced small (<0.1 MPa) pore pressure increases, indicating that the faults hosting these earthquakes are highly sensitive to changes in effective stress and have lower frictional stability than the 0.6 generally assumed. These results serve as a critical step in understanding the stress changes that induce earthquakes in one of the most seismically active and geologically complex basins in the US.